Retrieval of a Cold Welded and Damaged Gingival Former: A Clinical Tip - Unmesh Wani; Rajashree Jadhav; Paresh Gandhi; Bhushan Pol (Journal of Clinical and Diagnostic Research)
A 62-year-old male patient was referred to the Department of Prosthodontics at Bharati Vidyapeeth (Deemed to be University) Dental College and Hospital, Pune, Maharashtra, India, for the retrieval of a gingival former in the lower anterior region. An implant from COWELL® Implant Solution was placed in the regions of 33 and 43 at a private clinic approximately 11 months ago. The second stage surgery was performed seven months ago. Two gingival formers with a collar height of 2 mm were placed in the regions of 33 and 43. For the commencement of the prosthetic phase, the gingival formers needed to be removed.